Exploring the Operations Management of Rice Farmers: A Case Study in Molave, Zamboanga Del Sur: English - Gallano, Jessa; Sealza, Arha Mae D.; Basit, Jamby E.; Batingal, Ace Virgel Fiel T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study explored the operational management of rice farmers in Molave, Zamboanga del Sur, focusing on how they finance their farms and address farming needs from cultivation to harvest. Small to medium-sized rice farmers face increasing challenges related to funding, resource access, and labor practices. Understanding their management strategies provides insights into improving agricultural sustainability. A qualitative case study approach was employed, guided by Sharan B. Merriam’s methodology. Ten experienced rice farmers aged 25 and above, each operating farm for at least two years, participated in the study. Data were collected through semi-structured interviews, field observations, and audio recordings. The researchers served as the primary instruments of data collection, ensuring accuracy and contextual depth through transcription and thematic analysis. Findings revealed significant financial constraints among farmers, including limited access to credit, high operational costs for equipment, labor, fertilizers, and pesticides, and a lack of effective risk management practices. Additionally, unfair labor practices in rice trading were found to negatively impact farmer income and sustainability. Based on these findings, the study recommends that local governments enhance support for farmers by investing in agricultural infrastructure, organizing farmer associations, and providing free fertilizers and pesticides.Farmers are encouraged to engage in continuous learning and strengthen peer networks to build resilience. Future research should explore the broader impact of farm operations on local economies to inform policy and innovation. This study contributes to a deeper understanding of rice farming operations and highlights the need for targeted support to improve rural livelihoods.